2021
DOI: 10.3389/fpsyg.2021.755860
|View full text |Cite
|
Sign up to set email alerts
|

To Be Authentic, to Be Eco: Exploring the Link Between Authenticity and Pro-environmental Behavior

Abstract: Authentic self is believed to be morally good. The current research proposes that the authentic self is also environmentally good. Across two studies, we tested the link between authenticity and pro-environmental attitude and behavior. In Study 1 (N=2,646), dispositional authenticity was found to be a predictor of pro-environmental behavior (PEB). In Study 2 (N=474), participants in the authentic condition (recalling their experiences of being authentic) were more willing to donate money to protect the environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Ambarfebrianti & Novianty (2021), in their research with adolescent subjects, found that the value orientation adolescents possessed could predict pro-environmental behavior by 14%. Another research found that authenticity significantly correlated with pro-environmental behavior (Yang et al, 2021). Other research has also found that injunctive norms and normative goals could be relied on in encouraging environmental care behavior (Chakraborty et al, 2017;Pambudi & Wisuantari, 2021).…”
Section: Introductionmentioning
confidence: 95%
“…Ambarfebrianti & Novianty (2021), in their research with adolescent subjects, found that the value orientation adolescents possessed could predict pro-environmental behavior by 14%. Another research found that authenticity significantly correlated with pro-environmental behavior (Yang et al, 2021). Other research has also found that injunctive norms and normative goals could be relied on in encouraging environmental care behavior (Chakraborty et al, 2017;Pambudi & Wisuantari, 2021).…”
Section: Introductionmentioning
confidence: 95%